2016
DOI: 10.1080/19443994.2015.1030700
|View full text |Cite
|
Sign up to set email alerts
|

Pathway identification, enzyme activity and kinetic study for the biodegradation of phenol by Nocardia hydrocarbonoxydans NCIM 2386

Abstract: A B S T R A C TNocardia hydrocarbonoxydans NCIM 2386 (Nhy) can grow using phenol as a sole carbon source and has a strong ability to degrade phenol. The paper presents the main metabolism pathways and mechanism of phenol degradation by Nhy. Phenol was found to be degraded via meta cleavage of catechol by the action of enzyme catechol 2,3-dioxygenase. The enzyme was found to be both extracellular and cell bound. The cell bound and extracellular enzymes actively degraded phenol even in the absence of the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…able to degrade environmental pollutants, including several reports on their ability to degrade crude oil 12 – 14 . Furthermore, Shetty and Shetty 15 identified the pathway for the degradation of phenol by Nocardia hydrocarbonoxydans NCIM 2386, and Hristov et al . showed that a Nocardia sp.…”
Section: Introductionmentioning
confidence: 99%
“…able to degrade environmental pollutants, including several reports on their ability to degrade crude oil 12 – 14 . Furthermore, Shetty and Shetty 15 identified the pathway for the degradation of phenol by Nocardia hydrocarbonoxydans NCIM 2386, and Hristov et al . showed that a Nocardia sp.…”
Section: Introductionmentioning
confidence: 99%
“…; Hristov et al . ; Shetty and Shetty ). Although catechol has been isolated from Nocardia cell free extracts, only putative sequences of phenol 2‐monooxygenase have been reported (Engelhardt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia genus participates in the degradation of different hydrocarbons (Baek et al 2007;Rodrigues et al 2015). Species of this genus have demonstrated capability to degrade aromatic molecules, including phenol (Engelhardt et al 1979;Hanne et al 1993;Dabhade et al 2009;Ma et al 2010;Hristov et al 2014;Shetty and Shetty 2016). Although catechol has been isolated from Nocardia cell free extracts, only putative sequences of phenol 2-monooxygenase have been reported (Engelhardt et al 1979;Kaur et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Catechol is an important intermediate in the aerobic biodegradation of phenol (Rodriguez, et al, 2009), and the conversion of phenol to catechol by phenol hydroxylase is also a key step in determining the rate of phenol removal (Shetty, et al, 2015), so the in uence of catechol on the phenol degradation system is critical. The effect of different concentrations of catechol on the low-temperature phenol degradation system was investigated.…”
Section: Effect Of Intermediate Product Concentration On Biodegradati...mentioning
confidence: 99%